Atrial fibrillation as a contributor to the mortality in patients with dementia: A nationwide cohort study - Chen, Yun-Yu; Lin, Yenn-Jiang; Hsieh, Yu-Cheng; Chien, Kuo-Liong; Lin, Ching-Heng; Chung, Fa-Po; Chen, Shih-Ann (Frontiers in Cardiovascular Medicine, 2023)
Background Knowledge of the risk of death in patients with dementia is essential for planning preventive strategies. This study aimed to evaluate the effect of atrial fibrillation (AF) on death risks and other factors associated with death in patients with dementia and AF. Methods We conducted a nationwide cohort study using Taiwan's National Health Insurance Research Database. We identified subjects with dementia diagnosed for the first time and AF diagnosed concomitantly between 2013 and 2014. Subjects under the age of 18 years were excluded. Age, sex, and CHA2DS2-VASc scores were 1: 4 matched for AF patients (N = 1,679) and non-AF controls (N = 6,176) using the propensity score technique. The conditional Cox regression model and competing risk analysis were applied. The risk of mortality was tracked till 2019. Results AF history was associated with higher risks of all-cause death (hazard ratio [HR]: 1.208; 95% confidence interval [CI]: 1.142–1.277) and cardiovascular death (subdistribution HR: 1.210; 95% CI: 1.077–1.359) in dementia patients than patients without a diagnosis of AF. For patients with both dementia and AF, they had a higher risk of death due to higher age, diabetes mellitus, congestive heart failure, chronic kidney disease, and prior stroke. Anti-arrhythmic drugs and novel oral anticoagulants significantly reduced the risk of death in patients with AF and dementia. Conclusion This study found that AF is a risk factor for mortality in patients with dementia and explored several risk factors for AF-related mortality. This study highlights the importance of controlling AF especially in patients with dementia.